To solve the expression, we start by calculating the values inside the parentheses:
1.6^0 = 1 (for any number raised to the power of 0, the result is always 1)
7
Next, we calculate the result inside the parentheses:
1 + 7 = 8
Now, we substitute this value back into the expression:
2(8) - 4.9^0
Next, we calculate the value of the exponent:
4.9^0 = 1 (again, any number raised to the power of 0 is always 1)
Now, we substitute this value back into the expression:
2(8) - 1
Next, we perform the multiplication:
2 * 8 = 16
Now, we substitute this value back into the expression:
16 - 1
Finally, we subtract:
16 - 1 = 15
So, the expression simplifies to 15.
Solve the expression 2(1.6^0 + 7) -4.9^0
1 answer